Pengaruh Aktivitas Panahan terhadap Tingkat Konsentrasi pada Anak-Anak Sekolah Dasar - Oktafiranda, Nadya Dwi; Pelana, Ramdan; Mitsalina, Dinan; Diyananda, Dzulfiqar; Yuliana, Ela (Institut Teknologi Bandung, 2026)
Abstract Concentration is an important skill for elementary school children to support their learning success. This study aims to determine the effect of archery activities on the concentration levels of elementary school children. The research method used was a pre-experiment with a pretest and posttest one-group design. The research sample consisted of 15 children at SDN Duren Tiga 14 South Jakarta. Concentration levels were measured using the Concentration Grid Test (CGT). The results of the analysis showed a significant increase in concentration scores, with a pretest average of 2.33 and a posttest average of 9.47. Archery activities were proven to be effective in improving the concentration of elementary school children at SDN Duren Tiga 14, South Jakarta. Archery can be used as a means of cognitive stimulation in schools to improve children's concentration. Keywords: archery activities, archery sports, concentration. nd a posttest average of 9.47. Archery activities were proven to be effective in improving the concentration of elementary school children at SDN Duren Tiga 14, South Jakarta. Archery can be used as a means of cognitive stimulation in schools to improve children's concentration